Reclaiming the prince's heart - Winters, Rebecca, 1940- (Baldasseri royals., 2021)
"Can the prince fall back in love......with his forgotten princess? Luna can't believe it. Her husband, Prince Rini--the same man who had been reported dead after an earthquake--is alive...and standing right in front of her! Yet his return isn't the fairy-tale reunion that Luna always dreamed of. Why? Rini has amnesia and can't remember Luna--or their marriage! Will their still-powerful connection be strong enough to bring back the memory of their once-perfect love...?"--Back cover.